Over the counter CBD products in Germany: an exploratory survey about consumption patterns and health related effects - Weissgerber, Anaelle; Hermanns-Clausen, Maren; Lamy, Evelyn (Frontiers in Pharmacology, 2025)
Over-the-counter cannabidiol (CBD) products are showing substantial growth in marked share in recent years. However, the knowledge about health effects of these products is currently weak. In an explorative, retrospective online survey, the reasons for consumption, possible health-promoting or therapeutic effects, and adverse effects among CBD consumers in Germany were investigated. The anonymous questionnaire was accessible from 21 February 2023 to 20 June 2023. Participants (n = 208) were recruited mainly via social internet platforms. The study data was collected and managed using SoSci-Survey®. The study group was predominantly female (66%), between 41–60 years old (46%), and most of them were chronic CBD consumers (>3 months, at least daily). The principal mode of CBD use was oil (36%) with a CBD concentration between 10%–20%. Overall, the CBD products were mostly reported to have a positive effect on health. One of the main reasons for use was for improving physical and mental capacities. Here, the effect of CBD was rated effective for helping the general state of health (89%), and for the wellbeing (89%). In 79% of cases, the CBD product was rated as effective in alleviating disease symptoms. Improvements were reported especially in relief from pain (general, chronic, muscle and joint pain), or psychological symptoms (sleep disorders, nervousness, anxiety). Reported adverse effects were mainly dry mouth and sleepiness, but for 69% of the participants, no adverse effects were reported. A strong belief in the efficacy of dietary supplements, natural remedies, and CBD products among users suggests that expectation and placebo effects may have played a relevant role in the reported outcomes. This should be considered when interpreting the results and underlines the need for further controlled studies to differentiate pharmacological effects from psychological influences.